2008
DOI: 10.1596/1813-9450-4584
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls Of Participatory Programs: Evidence From A Randomized Evaluation In Education In India

Abstract: Participation of beneficiaries in the monitoring of public services is increasingly seen as a key to improving their efficiency. In India, the current government flagship program on universal primary education organizes both locally elected leaders and parents of children enrolled in public schools into committees and gives these groups powers over resource allocation, and monitoring and management of school performance. However, in a baseline survey we found that people were not aware of the existence of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 28 publications
7
94
0
Order By: Relevance
“…The biggest effect was on teacher presence and effort, whereas the impact on pupil learning was more modest. By contrast, in another RCT study on the impact of information on the ability of communities to engage in accountability mechanisms and subsequent impacts on quality of services in India, Banerjee et al (2010) show that providing information -about the education programme as well as the level of child achievement in literacy and numeracy -had little impact on engagement with the school system or demanding accountability. Rather, when community volunteers were trained to carry out remedial classes outside the classroom, it had a greater impact on children's literacy and numeracy skills.…”
Section: Information Disseminationmentioning
confidence: 75%
“…The biggest effect was on teacher presence and effort, whereas the impact on pupil learning was more modest. By contrast, in another RCT study on the impact of information on the ability of communities to engage in accountability mechanisms and subsequent impacts on quality of services in India, Banerjee et al (2010) show that providing information -about the education programme as well as the level of child achievement in literacy and numeracy -had little impact on engagement with the school system or demanding accountability. Rather, when community volunteers were trained to carry out remedial classes outside the classroom, it had a greater impact on children's literacy and numeracy skills.…”
Section: Information Disseminationmentioning
confidence: 75%
“…The nature of community involvement as well as quality indicators of community involvement (community buy in; fidelity of implementation) are important factors for results. For instance, Banerjee et al (2010) compared two types of community involvement-(a) training community members on reading assessment so that they know their children's reading status and (b) training on reading instruction strategies-and found no effect of the training on assessment but a positive effect of the training on reading instruction. Furthermore, several studies indicated substantial challenges in parents' and/or students' participation in community sessions such as parent workshops and student reading camps (e.g., Badiable, Guajardo, Fermin, & Robis, 2013;Brown, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions also vary in terms of involvement of the community in student learning. The vast majority of interventions target instruction in the school context only, whereas some incorporate community involvement to encourage literacyrelated activities in the children's homes and communities (e.g., Banerjee et al, 2010;Dowd & Friedlander, 2016;Friedlander & Goldenberg, 2016). According to the Ecological Systems Theory, interactions in multiple layers of environment shape human development (Bronfenbrenner, 1979), and therefore, children's daily interactions in their homes and communities beyond the school setting influence their learning, including literacy skills (Bracken & Fischel, 2008;Senechal, LeFevre, Thomas, & Daley, 1998).…”
mentioning
confidence: 99%
“…Given that politicians' incentives may not be aligned with the goal of improved service delivery, several studies over the past decade have investigated the potential for social accountability: conveying information about government service delivery directly to citizens in the hopes that they will demand better performance from frontline providers (Fox, 2015;World Bank, 2016). Conclusions from this research program have been mixed; one study shows that efforts to facilitate citizen monitoring improve service delivery and health outcomes (Björkman & Svensson, 2009;Björkman Nyqvist, de Walque, & Svensson, 2017), whereas other studies in the area of education have found null effects on citizen engagement, learning outcomes, and teacher effort (Banerjee, Banerji, Duflo, Glennerster, & Khemani, 2010;Lieberman, Posner, & Tsai, 2014). A general conclusion is that the effective exercise of social accountability is often inhibited by barriers to collective action, a low sense of efficacy, and a lack of knowledge of concrete steps that citizens can take to act upon information (Banerjee et al, 2010;Buntaine, Daniels, & Devlin, 2018;Fox, 2015;Lieberman et al, 2014).…”
Section: Principals Agents Citizens and Health Servicesmentioning
confidence: 98%